X-Ray tomographic characterisation of pitting corrosion in lean duplex stainless steel. (1st April 2020) - Eguchi, Kenichiro; Burnett, Timothy L; Engelberg, Dirk L
Graphical abstract: Highlights: Grain size dependent lacy pit covers were observed. Pitting corrosion occurred via selective dissolution. Pit morphology was grain size dependent. Pit stability products <0.3 Am −1 (as received) and <0.6 Am −1 (heat treated) were obtained. Abstract: The nucleation and growth of pitting corrosion in grade 2202 lean duplex stainless steel has been observed via X-ray Computed Tomography. The charge measured using an electro-chemical in-situ cell was correlated with pit growth characteristics and associated pit shape morphologies. Lacy metal covers were observed with holes formed by selective dissolution of the ferrite. All pits grew into semi-ellipsoid shapes, with large fractions of un-dissolved austenite grains remaining inside pits in heat-treated microstructures. For the as-received microstructure the stability product showed typical values below 0.3 Am −1, with larger stability values observed for the heat-treated sample.